Sonhos antecipatórios: influência de um evento significativo da vigília na atividade onírica - Scott, Rafael Neia Barbosa (2009)
In most cultures, dreams are believed to predict the future on occasion. Several neurophysiological studies indicate that the function of sleep and dreams is to consolidate and transform memories, in a cyclical process of creation, selection and generalization of conjectures about the reality. The aim of the research presented here was to investigate the possible adaptative role of anticipatory dreams. We sought to determine the relationship between dream and waking in a context in which the adaptive success of the individual was really at risk, in order to mobilize more strongly the oneiric activity. We used the entrance examination of the Federal University of Rio Grande do Norte (UFRN) as a significant waking event in which performance could be independently quantified. Through a partnership with UFRN, we contacted by e-mail 3000 candidates to the 2009 examination. In addition, 150 candidates were approached personally. Candidates who agreed to participate in the study (n = 94) completed questionnaires specific to the examination and were asked to describe their dreams during the examinaton period. The examination performance of each candidate in the entrance examination was provided by the UFRN to the researcher. A total of 45 participants reported dreams related to the examination. Our results show a positive correlation between performance on the examination and anticipatory dreams with the event, both in the comparison of performance on objective and discursive, and in final approval (in the group that not dreamed with the exam the rate of general approval, 22,45%, was similar to that found in the selection process as a whole, 22.19%, while for the group that dreamed with the examination that rate was 35.56%). The occurrence of anticipatory dreams reflectes increased concern during waking (psychobiological mobilization) related to the future event, as indicated by higher scores of fear and apprehension, and major changes in daily life, in patterns of mood and sleep, in the group that reported testrelated dreams. Furthermore, the data suggest a role of dreams in the determination of environmentally relevant behavior of the vigil, simulating possible scenarios of success (dream with approval) and failure (nightmares) to maximize the adaptive success of the individual